A case report of Pallister-Killian syndrome with an unusual mosaic supernumerary marker chromosome 12 with interstitial 12p13.1-p12.1 duplication - Karamysheva, T. V.; Lebedev, I. N.; Minaycheva, L. I.; Nazarenko, L. P.; Kashevarova, A. A.; Fedotov, D. A.; Skryabin, N. A.; Lopatkina, M. E.; Cheremnykh, A. D.; Fonova, E. A.; Nikitina, T. V.; Sazhenova, E. A.; et al. (Frontiers in Genetics, 2024)
Pallister-Killian syndrome (PKS) is a rare inherited disease with multiple congenital anomalies, profound intellectual disability, and the presence in the karyotype of sSMC -i(12)(p10). The frequency of PKS may be underestimated due to problems with cytogenetic diagnosis caused by tissue-specific mosaicism and usually a low percentage of peripheral blood cells containing sSMC. Such tissuespecific mosaicism also complicates a detailed analysis of the sSMC, which, along with the assessment of mosaicism in different tissues, is an important part of cytogenetic diagnosis in PKS. Unfortunately, a full-fledged diagnosis in PKS is either practically impossible or complicated. On the one hand, this is due to problems with the biopsy of various tissues (skin biopsy with fibroblast culture is most often used in practice); on the other -a low percentage of dividing peripheral blood cells containing sSMC, which often significantly complicates the analysis of its composition and organization.In the present study, a detailed analysis of sSMC was carried out in a patient with a characteristic clinical picture of PKS. A relatively high percentage of peripheral blood cells with sSMC (50%) made it possible to perform a detailed molecular cytogenetic analysis of de novo arisen sSMC using chromosomal in situ suppression hybridization (CISS-hybridization), multicolor FISH (mFISH), multicolor chromosome banding (MCB), array CGH (aCGH), and quantitative real-time PCR (qPCR), and short tandem repeat (STR) -analysis. As a result, it was found that the sSMC is not a typical PKS derivative of chromosome 12. In contrast to the classical i(12)(p10) for PKS, the patient's cells contained an acrocentric chromosome consisting of 12p material. Clusters of telomeric repeats were found at the both ends of the sSMC. Furthemore, the results of aCGH and qPCR indicate the presence of interstitial 8.9 Mb duplication at 12p13.1-p12.1 within the sSMC, which leads to different representations of DNA from different segments of 12p within cells that containing sSMC.The obtained data raise the question of the instability of the sSMC and, as a consequence, the possible presence of additional rearrangements, which, in traditional cytogenetic analysis of patients with PKS, are usually described as i(12)(p10).